Respuesta :

s1m0

You can do substitution 2x-2=x^2 -x -6; isolate all terms on one side 0= x^2 -x-2x -6+2; combine like terms x^2 -3x -4=0; factor the quadratic (x-4)(x+1)=0; each term is zero x-4=0 so x=4 and x+1=0 so x=-1. Now, y=2•4-2=6 and y=2•(-1) -2= -4 ; solutions for the system are ( 4,6) and ( -1, -4)

Answer:

(4,6) or (-1,-4)

Step-by-step explanation:

since both equations about x are equal to y, you can make x^2-x-6=2x-2

solve this quadratic equation, you get x=4 or -1

substitute x into y=2x-2

you get y=6 when x=4, or y= -4 when x=-1